2020
DOI: 10.1021/acs.orglett.0c03195
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis of Hydrazone and Oxime Peptide Ligation by Arginine

Abstract: Hydrazone and oxime peptide ligations are catalyzed by arginine. The catalysis is assisted intramolecularly by the side-chain guanidinium group. Hydrazone ligation in the presence of arginine proceeds efficiently in phosphate buffer at neutral pH but is particularly powerful in bicarbonate/CO2 buffer. In addition to acting as a catalyst, arginine prevents the aggregation of proteins during ligation. With its dual properties as a nucleophilic catalyst and a protein aggregation inhibitor, arginine hydrochloride … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The model cross-linking reaction between the nucleoside 2′-deoxyguanosine and 3 was carried out in a solvent mixture composed of 1:5 DMSO and HEPES buffer (50 mM, pH 7.4) containing arginine as a catalyst. , Chemical precedents provided by the reactions of 2′-deoxyguanosine with low molecular weight α,β-unsaturated aldehydes enabled us to suspect that this reaction would proceed via aza-Michael-type addition of the exocyclic N 2 -amino group of the guanine residue to the α,β-unsaturated sugar residue. ,, LC-MS analysis of the reaction revealed a mixture of isomeric products displaying the [M + H] + ion (at m / z 384 amu) anticipated for the nucleosidic ICL model 4 (Scheme ). NMR analyses of this mixture revealed signals consistent with 4 , but detailed assignment of the resonances was not possible due to the complexity of the spectra (up to 14 equilibrating isomers are possible for this product, four diastereomers of the O-cyclized pyranose form, four diastereomers of the O-cyclized furanose form, four diastereomers of the N-cyclized form, and two enantiomers of the ring-opened form).…”
Section: Resultssupporting
confidence: 56%
“…The model cross-linking reaction between the nucleoside 2′-deoxyguanosine and 3 was carried out in a solvent mixture composed of 1:5 DMSO and HEPES buffer (50 mM, pH 7.4) containing arginine as a catalyst. , Chemical precedents provided by the reactions of 2′-deoxyguanosine with low molecular weight α,β-unsaturated aldehydes enabled us to suspect that this reaction would proceed via aza-Michael-type addition of the exocyclic N 2 -amino group of the guanine residue to the α,β-unsaturated sugar residue. ,, LC-MS analysis of the reaction revealed a mixture of isomeric products displaying the [M + H] + ion (at m / z 384 amu) anticipated for the nucleosidic ICL model 4 (Scheme ). NMR analyses of this mixture revealed signals consistent with 4 , but detailed assignment of the resonances was not possible due to the complexity of the spectra (up to 14 equilibrating isomers are possible for this product, four diastereomers of the O-cyclized pyranose form, four diastereomers of the O-cyclized furanose form, four diastereomers of the N-cyclized form, and two enantiomers of the ring-opened form).…”
Section: Resultssupporting
confidence: 56%
“…The kinetic data could be fitted to an apparent second-order rate law (dashed lines). Based on the obtained rate constants, hydrazone formation proceeds ~3 times faster with the peptide reactants equipped with the charged modules ( 13a,a vs 13d,g ) when the catalyst is arginine (50 mM) 40 , and 13 times faster with aniline catalyst used at the same concentration. Another series of experiments were performed using a larger diversity of charged peptide modules and arginine as catalyst to enable the monitoring of hydrazone formation by UV spectroscopy (see Supplementary Methods, Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The reactions were conducted in phosphate buffer (50 mM) at neutral pH, in the presence of aniline 26 , 27 , 39 or arginine 40 acting as nucleophilic catalysts. The results of the kinetic study are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Formation of AP-derived ICLs likely proceeds via an imine intermediate (Figure A). Therefore, we examined whether inclusion of established imine-formation catalysts aniline (1 mM), , anthranilic acid (100 mM), arginine (1 mM), and N , N ′-dimethylethylenediamine (DMEDA, 20 mM) increased the rate of ICL formation in the AP-containing duplex 1a . We found that none of these agents served as effective catalysts for dA-AP cross-link formation (Table ).…”
Section: Resultsmentioning
confidence: 99%